Special Legal Solutions in the Sphere of Culture as an Expression of Care for the Dignity, Life and Health of Persons with Disabilities - Karcz-Kaczmarek, Maria (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of this article is the legal analysis of specific solutions established in the cultural sphere for the benefit of people with disabilities. These regulations are the implementation of national and international obligations, but, above all, they should be considered as an expression of concern for human dignity, life and health. Issues concerning the elimination of architectural barriers, the formation of pricing policies in the sphere of culture, and issues of accessibility of audio-visual programs for people with visual and hearing disabilities will be discussed.